Bio-Inspired Nanomaterials For Drug Delivery: Synthesis, Characterization, And Stimuli-Responsive Performance - Tripathi, Shushri Rekha; Shrivastava, Shilpi (Journal of Neonatal Surgery, 2025)
Bio-inspired nanomaterials have emerged as promising alternatives to conventional nan carriers for efficient and targeted drug delivery due to their enhanced biocompatibility and biomimetic functionality. This study investigates the feasibility of bio-inspired nanomaterials for drug delivery by developing biomimetic synthesis strategies, characterizing their physicochemical properties, and evaluating their drug delivery performance in comparison with conventional nanoparticles. Bio-inspired nanomaterial’s were synthesized using nature-derived polymers and self-assembly approaches to mimic biological structures, while conventional nanoparticles were prepared using standard chemical methods. Comprehensive characterization was performed using particle size analysis, zeta potential measurements, and spectroscopic techniques. The results demonstrate that bio-inspired nanomaterial’s exhibited a significantly smaller average particle size (95 ± 12 nm) and lower polydispersity index (0.18 ± 0.03) compared to conventional nanoparticles (180 ± 25 nm, PDI 0.38 ± 0.05), indicating improved nanoscale uniformity and stability. Enhanced surface charge (−28.6 ± 1.9 mV) further contributed to superior colloidal stability. Drug loading and encapsulation efficiencies of bio-inspired nanomaterial’s were markedly higher (84.7% and 88.9%, respectively) than those of conventional systems. In vitro release studies revealed controlled and sustained drug release (42.3% at 24 h) under physiological conditions, while stimuli-responsive behaviour enabled accelerated release in acidic and enzyme-rich environments. Biocompatibility assessment confirmed higher cell viability (92.6%) and significantly reduced hemolysis (2.1%), alongside improved cellular uptake (78.9%)...